The hardest butter to button: immediate context effects in spoken word identification. - Brock, J; Nation, K (2014)
According to some theories, the context in which a spoken word is heard has no impact on the earliest stages of word identification. This view has been challenged by recent studies indicating an interactive effect of context and acoustic similarity on language-mediated eye movements. However, an alternative explanation for these results is that participants looked less at acoustically similar objects in constraining contexts simply because they were looking more at other objects that were cued by the context. The current study addressed this concern whilst providing a much finer grained analysis of the temporal evolution of context effects. Thirty-two adults listened to sentences while viewing a computer display showing four objects. As expected, shortly after the onset of a target word (e.g., "button") in a neutral context, participants saccaded preferentially towards a cohort competitor of the word (e.g., butter). This effect was significantly reduced when the preceding verb made the competitor an unlikely referent (e.g., "Sam fastened the button"), even though there were no other contextually congruent objects in the display. Moreover, the time-course of these two effects was identical to within approximately 30 ms, indicating that certain forms of contextual information can have a near-immediate effect on word identification.